Frequent Home Monitoring of ICD Is Effective to Prevent Inappropriate Defibrillator Shock Delivery. (29th January 2014) - Bifulco, Paolo; Argenziano, Luigi; Romano, Maria; Cesarelli, Mario; Sansone, Mario; Casella, Stefano; Nardi, Stefano
Abstract : Recently, in the context of telemedicine, telemonitoring services are gaining attention. They are offered, for example, to patients with implantable cardioverter defibrillators (ICDs). A major problem associated with ICD therapy is the occurrence of inappropriate shocks which impair patients' quality of life and may also be arrhythmogenic. The telemonitoring can provide a valid support to intensify followup visits, in order to improve the prevention of inappropriate defibrillator shock, thus enhancing patient safety. Inappropriate shock generally depends on atrial fibrillation, supraventricular tachycardia, and abnormal sensing (such as those caused by electromagnetic interferences). As a practical example, an unusual case of an ICD patient who risked an inappropriate shock while taking a shower is reported. Continuous remote telemonitoring was able to timely warn cardiologist via GSM-SMS, who were able to detect improper sensing examining the intracardiac electrogram via Web. Patient was promptly contacted and warned to not further come in contact with the hydraulic system and any electrical appliance to prevent an inappropriate defibrillator shock. This demonstrates the effectiveness and usefulness of continuous remote telemonitoring in supporting ICD patients.